INVESTIGASI AREA SERRATED YIELDING PADA PADUAN 800H - I Made Wicaksana Ekaputra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Detailed information about the mechanical properties of components in the power plant was crucial in process design. One essential piece of information was the characteristics of the material at various temperatures in a tension load. In this study, the tensile test was applied to the Alloy 800H with various temperatures ranging from 24oC to 900oC at a constant deformation rate of 10-4/s. Alloy 800H was a promising candidate for components in power plants due to its high corrosion resistance in a high-temperature environment. A test was conducted by following the ASTM E8 and ASTM E21. The tensile apparatus was equipped with a furnace, and a thermocouple was attached to the specimen surface of the cylindrical during the test. The data was recorded by the data acquisition connected to the PC. This preliminary study aimed to determine the serrated yielding area that occurred based on several data from tensile test results.